Interface modification method for preparing negative-electrode-free lithium metal battery by utilizing ultraviolet polymerization tannic acid composite Ag particles

By using ultraviolet polymerized tanninic acid composite Ag particle technology on the negative electrode surface of the negative electrode without anode lithium metal battery, the polytanninic acid film and Ag particle channel is solved, and the problem of poor reversibility of negative electrode lithium nucleation barrier and lithium plating/lithium stripping is improved. The energy density and cycle stability of the battery are achieved.

CN119253094AActive Publication Date: 2025-01-03HARBIN UNIV OF SCI & TECH
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202411374851.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-29
Publication Date
2025-01-03
Estimated Expiration
2044-09-29

AI Technical Summary

Technical Problem

The existing negative electrode-free lithium metal batteries have poor lithium philtrum and poor reversibility when negative electrodes, which are difficult to meet the needs of high energy density.

Method used

UV polymerized tannin composite Ag particles are used to construct a polytannin film rich in polar functional groups on the surface of Cu foil, and Ag particle channels are established on the polytannin film and the surface of Cu foil are neutralized to form an elastic lithium-philic channel, which is optimized. Charge transfer process.

Benefits of technology

It effectively reduces the lithium nucleation barrier, improves the cycle stability of the battery and the reversibility of lithium plating/lithium stripping, inhibits the growth of lithium dendrites, and improves the mass and volume energy density of the battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119253094A_ABST
    Figure CN119253094A_ABST
Patent Text Reader

Abstract

The invention discloses an interface modification method for preparing a negative-electrode-free lithium metal battery by utilizing ultraviolet polymerization tannic acid composite Ag particles. The interface modification method is used for solving the problems that a negative electrode of a negative-electrode-free lithium metal battery in the prior art is poor in lithium affinity, relatively large in nucleation obstruction, non-uniform in lithium deposition, relatively poor in lithium stripping / plating reversibility and the like. The method comprises the specific steps that the Cu foil is placed in hydrochloric acid to be shaken and oscillated, and then deionized water and ethyl alcohol are used for repeatedly cleaning the Cu foil for three times; and preparing a phosphate buffer solution. Dispersing tannic acid in a phosphate buffer solution to obtain a polymerization solution; and the cleaned Cu foil is placed in a polymerization solution and irradiated by an ultraviolet lamp, and the Cu foil with the poly-tannic acid film on the surface is obtained. And the copper foil with the tannic acid film on the surface is further placed in an AgNO3 solution for reaction, and then the Cu foil with the poly-tannic acid film interface compounded with Ag particles is obtained. The poly-tannic acid thin film compounded with the Ag particles improves the interface of the Cu foil to a certain degree. Compared with the prior art, the method has the advantages that the lithium nucleation obstruction and the lithium nucleation overpotential of the Cu foil negative electrode are reduced, and the reversibility of plating / stripping lithium is enhanced, so that an SEI film formed at a negative electrode interface is more stable. And moreover, the generation of lithium dendrites can be effectively inhibited, the cycle performance and safety of the battery are improved, and the cycle service life of the battery is prolonged.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to an interface modification method for preparing a negative electrode-free lithium metal battery by utilizing ultraviolet polymerized tannic acid composite Ag particles. Background Art

[0002] As the energy density of lithium-ion batteries increases and their costs decrease, they are increasingly used in electric vehicles and portable electronic devices. Currently, commercial lithium-ion batteries usually use graphite based on the lithium-ion intercalation mechanism as the anode material. The specific energy density of batteries based on the lithium-ion intercalation mechanism has reached about 260Wh kg in recent years. -1 The peak soon approached 300Wh kg -1 The rapid development of electric vehicles has led to the demand for high energy density (500Wh kg -1 ), lithium-ion batteries with graphite as anode can no longer meet the demand for high energy density lithium-ion batteries. Therefore, the development of a new generation of lithium-ion batteries is imminent. The negative electrode-free lithium metal battery (AFLMB) that does not require additional lithium metal has come into people's view. In AFLMB, the current collector of materials such as Cu foil that do not contain active substances is retained only on the negative electrode side (only materials such as Cu foil that do not contain active substances are used as the negative electrode), making the N / P ratio close to 0. Compared with the graphite negative electrode, AFLMB reduces the mass and volume of the battery, increasing the mass energy density by 38.5% and the volume energy density by 85.5%. When NCM is used as the positive electrode and lithium foil is used as the negative electrode, the battery specific energy is 255Wh kg -1 , while the specific energy of the battery without negative electrode system can reach 392Wh kg -1 Summary of the invention

[0003] The purpose of the present invention is to solve the problems of poor lithium affinity and reversibility of lithium plating / stripping when preparing the negative electrode of a negative electrode-free lithium metal battery using existing methods, and to provide an interface modification method for preparing a negative electrode-free lithium metal battery using ultraviolet polymerized tannic acid composite Ag particles. A polytannic acid film rich in polar functional groups is constructed on the surface of Cu foil. Although the introduction of PTA reduces the lithium nucleation barrier (150mV for Cu foil, 25mV for polytannic acid film Cu thin film), the lower electronic conductivity slows down the kinetic process of the electrode surface reaction. We use the abundant phenolic hydroxyl groups in the polytannic acid film to convert the Ag in the AgNO3 solution into +Reduction, Ag particle channels are established in the polytannic acid film and on the Cu foil surface. The addition of Ag particles with excellent lithium affinity not only further reduces the lithium nucleation barrier (polytannic acid film composite Ag particles Cu foil 10mV), but also optimizes the charge transfer process. The polytannic acid film and Ag particles work synergistically to form an elastic lithium affinity channel, and the growth of lithium dendrites is inhibited. The process of UV-assisted rapid polymerization of tannic acid on the Cu surface has the advantages of good economy, short polymerization time, and low pollution, and is expected to be used in actual production.

[0004] 1. An interface modification method for preparing a negative electrode-free lithium metal battery using ultraviolet polymerized tannic acid composite Ag particles, characterized in that the method is carried out according to the following steps:

[0005] 1. Pretreatment of Cu foil

[0006] The Cu foil was placed in hydrochloric acid and shaken for 5 to 15 minutes, then washed three times with deionized water and ethanol, and then dried in a vacuum drying oven at 80 to 100°C.

[0007] 2. Preparation of phosphate buffer solution

[0008] Prepare a phosphate buffer solution consisting of sodium dihydrogen phosphate and disodium hydrogen phosphate, and stir evenly at room temperature;

[0009] 3. Preparation of polymerization solution

[0010] Add tannic acid to the phosphate buffer solution and control the tannic acid concentration to 0.2-1 g L -1 , stir evenly at room temperature;

[0011] 4. UV-assisted polymerization of tannic acid

[0012] Place the pretreated Cu foil in the polymerization solution. Irradiate it with a UV lamp for several minutes, then take it out. Wash it three times with deionized water and ethanol, and dry it in a vacuum drying oven at 80-100°C.

[0013] 5. Preparation of Ag particle composite solution

[0014] Take AgNO3 and dissolve it in water, stir it evenly to form AgNO3 solution, and set aside;

[0015] 6. Ag particle composite

[0016] Place the Cu foil with tannic acid film polymerized on the surface in AgNO3 solution, react for a certain period of time, and take it out after the reaction is completed. Wash it repeatedly with deionized water and ethanol three times, and put it into a vacuum drying oven at 80-100℃ for drying;

[0017] 7. Battery Assembly

[0018] After slicing the Cu foil obtained in step six, first place the negative electrode shell, and assemble the battery in the order of Cu foil, electrolyte, separator, electrolyte, Li sheet or lithium iron phosphate sheet, and positive electrode shell.

[0019] The phosphate buffer solution prepared in step 2 has a concentration of dihydrogen phosphate of 0.5 to 1 g L -1 , the concentration of disodium hydrogen phosphate is 1~3g L -1 .

[0020] Phosphate buffer solution of appropriate concentration can provide a more suitable environment for polymerization and promote the occurrence of polymerization reaction.

[0021] Furthermore, in step 4, the Cu foil is pretreated using hydrochloric acid of different concentrations.

[0022] The optimal concentration can be selected by comparing and observing the removal of the oxide film on the Cu foil surface. This can avoid the situation where the Cu foil surface morphology is rough or the oxide film is not completely removed due to excessively high or low hydrochloric acid concentration, which affects the reversibility of battery lithium plating / stripping.

[0023] Furthermore, the UV polymerization process in step 4 is carried out in a dark room.

[0024] In the darkroom, the influence of natural light and light on the polymerization process can be avoided. In the darkroom, the polytannic acid film can be spread evenly on the Cu foil surface to the greatest extent. The interface has high uniformity. Tannic acid is combined with buffer solution to reduce silver ions, effectively dispersing Ag nanospheres in the three-dimensional spatial network structure of polytannic acid. This polymer three-dimensional network structure is combined with Ag atoms to effectively construct a lithium-philic channel. This smooth channel is an effective way to ensure that there are no lithium dendrites and dead lithium. The reason is that the three-dimensional diffusion channel prevents energy accumulation, and the polymer framework prevents the tip effect, thereby effectively alleviating the uneven lithium plating / stripping caused by the local current density concentration during the battery cycle.

[0025] Furthermore, in step 4, the irradiation time of the ultraviolet lamp is controlled within 10 to 30 minutes.

[0026] Controlling the UV lamp irradiation time can control the thickness of the polytannic acid film on the Cu foil. If the film thickness is too thin, it will have poor mechanical strength and crack after multiple cycles, resulting in decreased cycle performance. If the film is too thick, it will increase the hindrance of lithium ion migration and decrease the electrode interface reaction rate.

[0027] Furthermore, in step 5, the concentration of the AgNO3 solution is 1 to 10 mmol·L -1 .

[0028] The concentration of AgNO3 solution is related to the uniformity of Ag particles. Selecting the appropriate concentration can form a uniform Ag particle channel in Cu foil and polytannic acid. Uniformly distributed Ag particles can effectively reduce the concentration of local current density, reduce the lithium nucleation barrier, and improve the cycle stability of the battery.

[0029] Furthermore, the electrolyte used in the battery assembly in step 7 is 1 mol·L -1 LiPF6 was dissolved in DEC / FEC (1:1, V:V) and 1 mol·L -1 LiTFSI is dissolved in one or both of the mixed electrolytes DOL / DME (1:1, V:V).

[0030] Different electrolytes have different affinities for lithium and the voltage ranges they can adapt to. Selecting an appropriate electrolyte can improve the battery cycle stability.

[0031] The present invention has the following beneficial effects:

[0032] A polytannic acid film rich in polar functional groups was constructed on the surface of Cu foil. The introduction of the polytannic acid film reduced the lithium nucleation barrier (Cu 150mV, polytannic acid film Cu foil 25mV). The abundant phenolic hydroxyl groups in the polytannic acid film were used to establish Ag particle channels in the polytannic acid film and on the surface of Cu foil. The addition of Ag particles with excellent lithium affinity not only further reduced the lithium nucleation barrier (polytannic acid film composite Ag particles Cu foil 10mV), but also optimized the charge transfer process. The polytannic acid film and Ag particles synergistically formed an elastic lithium affinity channel, and the growth of lithium dendrites was inhibited. The process of rapid polymerization of tannic acid on the Cu surface assisted by UV has the advantages of good economy, short polymerization time, and low pollution, and is expected to be applied in actual production. BRIEF DESCRIPTION OF THE DRAWINGS

[0033] Figure 1 The adsorption energy of lithium ions by Cu foil, Ag particles and LiAg alloy in an interface modification method for preparing anode-free lithium metal batteries using ultraviolet polymerized tannic acid composite Ag particles;

[0034] Figure 2 This is a negative electrode nucleation overpotential curve obtained by an interface modification method for preparing a negative electrode-free lithium metal battery using ultraviolet polymerized tannic acid composite Ag particles;

[0035] Figure 3 The average efficiency diagram of negative electrode plating / stripping lithium obtained by an interface modification method for preparing negative electrode-free lithium metal battery using UV polymerized tannic acid composite Ag particles;

[0036] Figure 4The Tafel curve of a half-cell composed of a negative electrode and a lithium sheet prepared by an interface modification method for preparing a negative electrode-free lithium metal battery using ultraviolet polymerized tannic acid composite Ag particles;

[0037] Figure 5 The impedance diagram of a half-cell composed of a negative electrode and a lithium sheet prepared by an interface modification method for preparing a negative electrode-free lithium metal battery using ultraviolet polymerized tannic acid composite Ag particles;

[0038] Figure 6 This is the impedance diagram of the negative electrode half-cell prepared in Comparative Example 1 of the present invention;

[0039] Figure 7 This is the impedance diagram of the negative electrode half-cell prepared in Comparative Example 2 of the present invention;

[0040] Figure 8 This is the impedance diagram of the negative electrode half-cell prepared in Comparative Example 3 of the present invention;

[0041] Fig. 9 This is the impedance diagram of the negative electrode half-cell prepared in Comparative Example 4 of the present invention;

[0042] Fig.10 This is the impedance diagram of the negative electrode half-cell prepared in Comparative Example 5 of the present invention;

[0043] Fig.11 This is the impedance diagram of the negative electrode half-cell prepared in Comparative Example 6 of the present invention;

[0044] Fig.12 The voltammogram of the full battery cycle composed of the negative electrode and lithium iron phosphate is prepared by an interface modification method for preparing a negative electrode-free lithium metal battery using ultraviolet polymerized tannic acid composite Ag particles;

[0045] Fig.13 This is a cyclic voltammetry curve of a lithium iron phosphate full battery prepared in Comparative Example 1 of the present invention;

[0046] Fig.14 This is an in-situ impedance spectrum of a lithium iron phosphate half-cell during the initial cycle, which is prepared by an interface modification method for preparing a negative-electrode-free lithium metal battery using UV-polymerized tannic acid composite Ag particles.

[0047] Fig.15 This is the in-situ impedance spectrum of the lithium iron phosphate half-cell prepared in Comparative Example 1 of the present invention during the initial cycle;

[0048] Fig.16 The electronic conductivity diagram of the negative electrode is prepared by an interface modification method for preparing a negative electrode-free lithium metal battery using ultraviolet polymerized tannic acid composite Ag particles;

[0049] Fig.17The negative electrode electronic conductivity diagram prepared for comparative example 1 of the present invention;

[0050] Fig.18 The efficiency-specific capacity curve of a lithium iron phosphate half-cell cycled at 0.5C is obtained by using an interface modification method for preparing a negative electrode-free lithium metal battery using ultraviolet polymerized tannic acid composite Ag particles;

[0051] Fig.19 This is an efficiency-specific capacity curve of the lithium iron phosphate full battery prepared in Comparative Example 1 of the present invention when cycled at 0.5C;

[0052] Fig. 20 This is an efficiency-specific capacity curve of the lithium iron phosphate full battery prepared in Comparative Example 2 of the present invention when cycled at 0.5C;

[0053] Fig.21 This is an efficiency-specific capacity curve of the lithium iron phosphate full battery prepared in Comparative Example 3 of the present invention when cycled at 0.5C;

[0054] Fig. 22 This is an efficiency-specific capacity curve of the lithium iron phosphate full battery prepared in Comparative Example 4 of the present invention when cycled at 0.5C;

[0055] Fig.23 This is an efficiency-specific capacity curve of the lithium iron phosphate full battery prepared in Comparative Example 5 of the present invention when cycled at 0.5C;

[0056] Fig.24 This is an efficiency-specific capacity curve of the lithium iron phosphate full battery prepared in Comparative Example 6 of the present invention when cycled at 0.5C;

[0057] Fig.25 The specific capacity-voltage curve of a lithium iron phosphate full battery cycled at 0.5C is obtained by using an interface modification method for preparing a negative electrode-free lithium metal battery using ultraviolet polymerized tannic acid composite Ag particles;

[0058] Fig.26 The specific capacity-voltage curve of the lithium iron phosphate full battery prepared in Comparative Example 1 of the present invention when cycled at 0.5C;

[0059] Fig. 27 The specific capacity-voltage curve of the lithium iron phosphate full battery prepared in Comparative Example 2 of the present invention when cycled at 0.5C;

[0060] Fig.28 The specific capacity-voltage curve of the lithium iron phosphate full battery prepared in Comparative Example 3 of the present invention when cycled at 0.5C;

[0061] Fig.29 The specific capacity-voltage curve of the lithium iron phosphate full battery prepared in Comparative Example 4 of the present invention when cycled at 0.5C;

[0062] Fig.30 The specific capacity-voltage curve of the lithium iron phosphate full battery prepared in Comparative Example 5 of the present invention cycled at 0.5C;

[0063] Fig.31 This is a specific capacity-voltage curve of the lithium iron phosphate full battery prepared in Comparative Example 6 of the present invention when cycled at 0.5C. DETAILED DESCRIPTION

[0064] The present invention will be further described below in conjunction with the best embodiments, but the protection scope of the present invention is not limited to the following embodiments.

[0065] Experimental drugs

[0066]

[0067]

[0068] Experimental drugs

[0069]

[0070] Experimental example

[0071] Cu foil was placed in 1 mol·L -1 Shake in hydrochloric acid for 10 minutes, then wash three times with deionized water and ethanol, and dry in a vacuum oven at 80°C. The concentration is 0.6 g L -1 Sodium dihydrogen phosphate and 1.2 g L -1 Disodium hydrogen phosphate solution, stir evenly at room temperature. Add tannic acid to the phosphate buffer solution and control the tannic acid concentration to 0.2 g L -1 , stir evenly at room temperature. Place the pretreated Cu foil in the polymerization solution. Irradiate with the upper UV lamp for 10 minutes and then take it out. Wash it three times with deionized water and ethanol, and dry it in a vacuum drying oven at 80°C. Prepare a concentration of 5mmol·L -1 AgNO3 solution, place the Cu foil with tannic acid film polymerized on the surface in the AgNO3 solution, and take it out after the reaction is completed. Use deionized water and ethanol to wash it three times, and put it into a vacuum drying oven to dry at 80℃. After the obtained copper foil is sliced, it is assembled in a glove box filled with argon in the order of negative electrode shell, copper foil, diaphragm, lithium sheet or lithium iron phosphate electrode sheet, gasket, spring and positive electrode shell. The electrolyte used is 1mol·L -1 LiPF6 was dissolved in DEC / FEC (1:1, V:V).

[0072] Comparative Example 1

[0073] Cu foil was placed in 2 mol·L-1 Shake in hydrochloric acid for 10 minutes, then wash three times with deionized water and ethanol, and dry in a vacuum oven at 80°C. The concentration is 0.6 g L -1 Sodium dihydrogen phosphate and 1.2 g L -1 Disodium hydrogen phosphate solution, stir evenly at room temperature. Add tannic acid to the phosphate buffer solution and control the tannic acid concentration to 0.2 g L -1 , stir evenly at room temperature. Place the pretreated Cu foil in the polymerization solution. Irradiate with the upper UV lamp for 10 minutes and then take it out. Wash it three times with deionized water and ethanol, and dry it in a vacuum drying oven at 80°C. Prepare a concentration of 5mmol·L -1 The Cu foil with the tannic acid film polymerized on the surface was placed in the AgNO3 solution and taken out after the reaction was completed. The Cu foil was repeatedly washed with deionized water and ethanol for three times and dried in a vacuum drying oven at 80°C.

[0074] Comparative Example 2

[0075] Cu foil was placed in 1 mol·L -1 Shake in hydrochloric acid for 10 minutes, then wash three times with deionized water and ethanol, and dry in a vacuum oven at 80°C. The concentration is 0.6 g L -1 Sodium dihydrogen phosphate and 1.2 g L -1 Disodium hydrogen phosphate solution, stir evenly at room temperature. Add tannic acid to the phosphate buffer solution and control the tannic acid concentration to 0.2 g L -1 , stir evenly at room temperature. Place the pretreated Cu foil in the polymerization solution. Irradiate with the upper UV lamp in the dark room for 10 minutes, then take it out. Wash it three times with deionized water and ethanol, and dry it in a vacuum drying oven at 80°C. Prepare a concentration of 5mmol·L -1 The Cu foil with the tannic acid film polymerized on the surface was placed in the AgNO3 solution and taken out after the reaction was completed. The Cu foil was repeatedly washed with deionized water and ethanol for three times and dried in a vacuum drying oven at 80°C.

[0076] Comparative Example 3

[0077] Cu foil was placed in 1 mol·L -1 Shake in hydrochloric acid for 10 minutes, then wash three times with deionized water and ethanol, and dry in a vacuum oven at 80°C. The concentration is 0.6 g L -1 Sodium dihydrogen phosphate and 1.2 g L -1 Disodium hydrogen phosphate solution, stir evenly at room temperature. Add tannic acid to the phosphate buffer solution and control the tannic acid concentration to 0.2 g L -1, stir evenly at room temperature. Place the pretreated Cu foil in the polymerization solution. Irradiate with the upper UV lamp for 30 minutes and then take it out. Wash it three times with deionized water and ethanol, and dry it in a vacuum drying oven at 80°C. Prepare a concentration of 5mmol·L -1 The Cu foil with the tannic acid film polymerized on the surface was placed in the AgNO3 solution and taken out after the reaction was completed. The Cu foil was repeatedly washed with deionized water and ethanol for three times and dried in a vacuum drying oven at 80°C.

[0078] Comparative Example 4

[0079] Cu foil was placed in 1 mol·L -1 Shake in hydrochloric acid for 10 minutes, then wash three times with deionized water and ethanol, and dry in a vacuum oven at 80°C. The concentration is 0.6 g L -1 Sodium dihydrogen phosphate and 1.2 g L -1 Disodium hydrogen phosphate solution, stir evenly at room temperature. Add tannic acid to the phosphate buffer solution and control the tannic acid concentration to 0.2 g L -1 , stir evenly at room temperature. Place the pretreated Cu foil in the polymerization solution. Irradiate with the upper UV lamp for 10 minutes and then take it out. Wash it three times with deionized water and ethanol, and dry it in a vacuum drying oven at 80°C. Prepare a concentration of 10mmol·L -1 The Cu foil with the tannic acid film polymerized on the surface was placed in the AgNO3 solution and taken out after the reaction was completed. The Cu foil was repeatedly washed with deionized water and ethanol for three times and dried in a vacuum drying oven at 80°C.

[0080] Comparative Example 5

[0081] Cu foil was placed in 1 mol·L -1 Shake in hydrochloric acid for 10 minutes, then wash three times with deionized water and ethanol, and dry in a vacuum oven at 80°C. The concentration is 0.6 g L -1 Sodium dihydrogen phosphate and 1.2 g L -1 Disodium hydrogen phosphate solution, stir evenly at room temperature. Add tannic acid to the phosphate buffer solution and control the tannic acid concentration to 0.2 g L -1 , stir evenly at room temperature. Place the pretreated Cu foil in the polymerization solution. Irradiate with the upper UV lamp for 10 minutes and then take it out. Wash it three times with deionized water and ethanol, and dry it in a vacuum drying oven at 80°C. Prepare a concentration of 5mmol·L -1 The Cu foil with the tannic acid film polymerized on the surface was placed in the AgNO3 solution and reacted for 30 minutes. After the reaction, it was taken out, washed three times with deionized water and ethanol, and dried in a vacuum drying oven at 80°C.

[0082] Comparative Example 6

[0083] Cu foil was placed in 1 mol·L -1 Shake in hydrochloric acid for 10 minutes, then wash three times with deionized water and ethanol, and dry in a vacuum oven at 80°C. The concentration is 0.6 g L -1 Sodium dihydrogen phosphate and 1.2 g L -1 Disodium hydrogen phosphate solution, stir evenly at room temperature. Add tannic acid to the phosphate buffer solution and control the tannic acid concentration to 0.2 g L -1 , stir evenly at room temperature. Place the pretreated Cu foil in the polymerization solution. Irradiate with the upper UV lamp for 10 minutes and then take it out. Wash it three times with deionized water and ethanol, and dry it in a vacuum drying oven at 80°C. Prepare a concentration of 5mmol·L -1 AgNO3 solution, place the Cu foil with tannic acid film polymerized on the surface in the AgNO3 solution, and take it out after completion. Use deionized water and ethanol to wash it three times, and put it into a vacuum drying oven to dry at 80℃. After the obtained copper foil is sliced, it is assembled in the order of negative electrode shell, copper foil, diaphragm, lithium sheet (lithium iron phosphate positive electrode sheet), gasket, shrapnel and positive electrode shell in a glove box filled with argon. The electrolyte used is 1mol·L -1 LiTFSI was dissolved in DOL / DME (1:1, V:V).

[0084] Figure 1 In the interface modification method of preparing negative-electrode-free lithium metal batteries using ultraviolet polymerized tannic acid composite Ag particles, the adsorption energy of lithium ions on Cu foil, Ag particles and LiAg alloy was calculated by density functional theory, and the adsorption energy of lithium ions on the copper surface was only -0.54eV, which was much lower than the adsorption energy of lithium ions on the Ag (-1.53eV) and LiAg (-1.43eV) surfaces. The larger adsorption energy means that Ag and LiAg have better lithium affinity and smaller barriers during lithium deposition. Lithium ions first combine with Ag to form LiAg alloy during deposition. When all Ag particles are converted into LiAg alloy, the low nucleation barrier of LiAg can continue to play a role in uniform lithium deposition.

[0085] Figure 2 This is a negative electrode nucleation overpotential curve obtained by an interface modification method for preparing a negative electrode-free lithium metal battery using UV-polymerized tannic acid composite Ag particles. The assembled Li||Cu battery is at 1 mAh·cm -2The lithium nucleation overpotential of the electrode was tested at a current density of . The nucleation overpotential of the bare Cu foil is 150mV. Thanks to the abundant lithium-philic groups in tannic acid and good wettability, the lithium nucleation overpotential of a layer of polytannic acid film polymerized on the Cu surface is reduced to 25mV. After the introduction of Ag particles, an obvious alloying process can be observed on the nucleation curve, which is the process of Ag combining with lithium ions to generate LiAg. The nucleation overpotential of the polytannic acid film composite Ag particle Cu foil is further reduced to 10mV. This means that the lithium deposition on the surface of the polytannic acid film composite Ag particle Cu foil is minimal, and the growth of lithium dendrites and dead lithium will be inhibited.

[0086] Figure 3 This is a graph of the average efficiency of negative electrode lithium plating / stripping obtained by an interface modification method for preparing negative electrode-free lithium metal batteries using ultraviolet polymerized tannic acid composite Ag particles. The faster reaction kinetics and smaller lithium nucleation barrier make the average CE of lithium plating / stripping on polytannic acid film Cu foil (99.1%) and polytannic acid film composite Ag particle Cu foil (98.2%) higher than that of Cu (91.7%), showing better lithium plating reversibility. The average CE is reduced after the introduction of Ag particles. This is because during lithium plating, part of the lithium ions are first consumed to react with Ag to form LiAg alloy, and this part of the lithium ions will no longer be detached. Figure 3 It can also be seen that the polarization level of the polytannic acid film composite Ag particles Cu foil is the lowest during lithium plating / stripping, which indicates that its interface reaction is more stable.

[0087] Figure 4 This is a Tafel curve of a half-cell composed of a negative electrode and a lithium sheet prepared by an interface modification method for preparing a negative electrode-free lithium metal battery using ultraviolet polymerized tannic acid composite Ag particles. The Tafel plot also shows that polytannic acid film Cu foil and polytannic acid film composite Ag particle Cu foil can effectively improve the reaction kinetics during lithium plating / stripping. When the exchange current density is large, the redox reaction rate at the electrode is fast and the polarization level is low. The exchange current density of polytannic acid film Cu foil is 12.5 mA cm -2 Much higher than 5.2 mA cm of Cu -2 On this basis, the polytannic acid film composited with Ag particles and Cu foil further increased the exchange current density to 20.1 mA cm -2 .

[0088] Figure 5 The impedance diagram of the half-cell composed of the negative electrode and the lithium sheet prepared by the interface modification method of preparing a negative electrode-free lithium metal battery using UV polymerized tannic acid composite Ag particles, R ct =157.3Ω.

[0089] Figure 6The impedance diagram of the negative electrode half-cell prepared in Comparative Example 1 of the present invention, R ct =68.1Ω.

[0090] Figure 7 The impedance diagram of the negative electrode half-cell prepared in Comparative Example 2 of the present invention, R ct =34.4Ω.

[0091] Figure 8 The impedance diagram of the negative electrode half-cell prepared in Comparative Example 3 of the present invention, R ct =23.7Ω.

[0092] Fig. 9 The impedance diagram of the negative electrode half-cell prepared in Comparative Example 4 of the present invention, R ct =58.6Ω.

[0093] Fig.10 The impedance diagram of the negative electrode half-cell prepared in Comparative Example 5 of the present invention, R ct =51.7Ω.

[0094] Fig.11 The impedance diagram of the negative electrode half-cell prepared in Comparative Example 6 of the present invention, R ct =18.2Ω.

[0095] Fig.12 This is an interface modification method for preparing a negative electrode-free lithium metal battery using UV-polymerized tannic acid composite Ag particles. The voltammetric curve of the full battery cycle composed of the negative electrode and lithium iron phosphate is obtained. When the scan rate is 0.8mV·s -1 The redox peak positions differ by 1.02 V.

[0096] Fig.13 This is the cyclic voltammetry curve of the lithium iron phosphate full battery prepared in Comparative Example 1 of the present invention. When the scan rate is 0.8 mV·s -1 The redox peak position difference is 0.62V, which indicates that the oxide film on the surface of Cu foil can be effectively removed and the reaction rate at the electrode interface can be accelerated after cleaning with hydrochloric acid of appropriate concentration.

[0097] Fig.14 This is an in-situ impedance spectrum of a lithium iron phosphate half-cell during the initial cycle, which is prepared by an interface modification method for preparing a negative electrode-free lithium metal battery using ultraviolet polymerized tannic acid composite Ag particles. During the charge and discharge process, the battery impedance value is large and the impedance variation range is large.

[0098] Fig.15 This is the in-situ impedance spectrum of the lithium iron phosphate half-cell prepared in Comparative Example 1 of the present invention during the initial cycle. The battery impedance value is small, and the impedance variation range is small during the charge and discharge process, indicating that the electrode is more stable during the reaction process.

[0099] Fig.16 The electronic conductivity diagram of the negative electrode prepared by an interface modification method for preparing a negative electrode-free lithium metal battery using UV-polymerized tannic acid composite Ag particles is shown in Figure 1. s =0.34A.

[0100] Fig.17 The negative electrode electronic conductivity diagram prepared for Comparative Example 1 of the present invention is shown in FIG. s =0.35A.

[0101] Fig.18 The efficiency-specific capacity curve of a lithium iron phosphate half-cell cycled at 0.5C is obtained by an interface modification method for preparing a negative electrode-free lithium metal battery using ultraviolet polymerized tannic acid composite Ag particles; the capacity retention rate after 50 cycles is 17.5%.

[0102] Fig.19 This is the efficiency-specific capacity curve of the lithium iron phosphate full battery prepared in comparative example 1 of the present invention at 0.5C. After 50 cycles, the capacity retention rate is 21.2%. After using hydrochloric acid of appropriate concentration to remove the oxide film, the reaction between lithium ions and copper oxide is avoided, so that the electrode cycle reversibility is increased.

[0103] Fig. 20 This is the efficiency-specific capacity curve of the lithium iron phosphate full battery prepared in comparative example 2 of the present invention at 0.5C; the capacity retention rate after 50 cycles is 35.3%. Polymerization in a dark room can improve the uniformity of the polytannic acid film, reduce the occurrence of local current density concentration, and improve the reversibility of electrode lithium plating.

[0104] Fig.21 The efficiency-specific capacity curve of the lithium iron phosphate full battery prepared in comparative example 3 of the present invention at 0.5C cycle is shown; the capacity retention rate after 50 cycles is 36.1%. The thickness of the polytannic acid film can be controlled by controlling the ultraviolet polymerization time, and the appropriate thickness can effectively protect the electrode and promote lithium ion migration.

[0105] Fig. 22 The efficiency-specific capacity curve of the lithium iron phosphate full battery prepared in comparative example 4 of the present invention at 0.5C cycle; the capacity retention rate after 50 cycles is 38.1%. The concentration of AgNO3 solution will affect the aggregation degree of Ag particles. Too high a concentration will cause Ag particles to aggregate, thereby concentrating the local current density and leading to the formation of lithium dendrites. Too low a concentration will reduce the content of Ag particles in the negative electrode, affecting the electrode performance.

[0106] Fig.23The efficiency-specific capacity curve of the lithium iron phosphate full battery prepared in comparative example 5 of the present invention at 0.5C cycle; the capacity retention rate after 50 cycles is 40.1%. The reaction time in AgNO3 will affect the content of Ag particles in the negative electrode. If the reaction time is too short, the distribution of Ag particles will be uneven. Appropriate reaction time can evenly distribute Ag particles and improve the uniformity of the electrode surface.

[0107] Fig.24 This is the efficiency-specific capacity curve of the lithium iron phosphate full battery prepared in comparative example 6 of the present invention at 0.5C; the capacity retention rate after 50 cycles is 49.4%. The use of a suitable electrolyte can provide more favorable conditions for lithium ion migration during the battery cycle and improve the reversibility of electrode lithium plating.

[0108] Fig.25 This is a specific capacity-voltage curve of a lithium iron phosphate full battery cycled at 0.5C, which is prepared by an interface modification method for preparing a negative electrode-free lithium metal battery using ultraviolet polymerized tannic acid composite Ag particles. After 50 cycles, the battery polarization voltage is 0.68.

[0109] Fig.26 The specific capacity-voltage curve of the lithium iron phosphate full battery prepared in comparative example 1 of the present invention at 0.5C cycle is shown. After 50 cycles, the battery polarization voltage is 0.63 V. Using hydrochloric acid with a higher concentration can more completely remove the oxide layer on the surface of the copper foil, accelerate the electrode interface reaction rate, and reduce the polarization voltage.

[0110] Fig. 27 The specific capacity-voltage curve of the lithium iron phosphate full battery prepared in comparative example 2 of the present invention at 0.5C cycle is shown. After 50 cycles, the battery polarization voltage is 0.28 V. UV polymerization in a dark room can induce more uniform formation of polytannic acid film on the surface of Cu foil, which is beneficial to reduce the battery polarization voltage.

[0111] Fig.28 The specific capacity-voltage curve of the lithium iron phosphate full battery prepared in comparative example 3 of the present invention at 0.5C cycle is shown. After 50 cycles, the battery polarization voltage is 0.17 V. By extending the ultraviolet irradiation time, a more complete and solid polytannic acid film can be constructed on the copper foil surface, and more elastic Ag particle channels are formed during the reaction process, which is beneficial to reducing the battery polarization voltage.

[0112] Fig.29 The specific capacity-voltage curve of the lithium iron phosphate full battery prepared in comparative example 4 of the present invention at 0.5C cycle is shown. After 50 cycles, the battery polarization voltage is 0.89 V. The use of a higher concentration of AgNO3 solution will accelerate the reduction process, resulting in significantly uneven distribution of Ag particle channels on the copper foil, which leads to an increase in the battery polarization voltage.

[0113] Fig.30 The specific capacity-voltage curve of the lithium iron phosphate full battery prepared in comparative example 5 of the present invention at 0.5C cycle is shown. After 50 cycles, the polarization voltage of the battery is 0.22 V. Prolonging the immersion time in the AgNO3 solution can build sufficient Ag particle channels in the polytannic acid film on the copper foil surface, thereby reducing the polarization voltage of the battery.

[0114] Fig.31 This is the specific capacity-voltage curve of the lithium iron phosphate full battery prepared in comparative example 6 of the present invention under 0.5C cycle. After 50 cycles, the battery polarization voltage is 0.38V. -1 LiTFSI dissolved in DOL / DME (1:1, V:V) as the electrolyte has a better affinity for lithium metal, forming a more stable SEI film and reducing the polarization voltage of the battery.

Claims

1. An interface modification method for preparing a negative electrode-free lithium metal battery using ultraviolet polymerized tannic acid composite Ag particles, characterized in that The method described is carried out according to the following steps:

1. Pretreatment of Cu foil The Cu foil was placed in hydrochloric acid and shaken for 5 to 15 minutes, then washed three times with deionized water and ethanol, and then dried in a vacuum drying oven at 80 to 100°C.

2. Preparation of phosphate buffer solution Prepare a phosphate buffer solution consisting of sodium dihydrogen phosphate and disodium hydrogen phosphate, and stir evenly at room temperature; 3. Preparation of polymerization solution Add tannic acid to the phosphate buffer solution and control the tannic acid concentration to 0.2-1 g L -1 , stir evenly at room temperature; 4. UV-assisted polymerization of tannic acid The pretreated Cu foil was placed in the polymerization solution; after being irradiated with a UV lamp, it was taken out; it was repeatedly washed with deionized water and ethanol three times, and dried in a vacuum drying oven at 80-100°C; 5. Preparation of Ag particle composite solution Take AgNO3 and dissolve it in water, stir it evenly to form AgNO3 solution, and set aside; 6. Ag particle composite The Cu foil with tannic acid film polymerized on the surface was placed in AgNO3 solution for a certain period of time. After the reaction was completed, it was taken out; it was repeatedly washed with deionized water and ethanol three times, and then placed in a vacuum drying oven at 80-100°C for drying; 7. Battery Assembly After slicing the Cu foil obtained in step six, first place the negative electrode shell, and assemble the battery in the order of Cu foil, electrolyte, separator, electrolyte, Li sheet or lithium iron phosphate sheet, and positive electrode shell.

2. An interface modification method for preparing a negative electrode-free lithium metal battery using ultraviolet polymerized tannic acid composite Ag particles, characterized in that The interface of the negative electrode-free lithium metal battery prepared by the ultraviolet polymerized tannic acid composite Ag particles is a Cu foil negative electrode interface; the polytannic acid is polymerized by ultraviolet assistance, and the polymerization solution is composed of tannic acid, sodium dihydrogen phosphate, disodium hydrogen phosphate and water.

3. The method for preparing an interface modification of a negative electrode-free lithium metal battery using ultraviolet polymerized tannic acid composite Ag particles according to claim 1, characterized in that The concentration of sodium dihydrogen phosphate in the polymerization solution is 0.5-1 g L -1 , the concentration of disodium hydrogen phosphate is 1~3g L -1 .

4. The method for preparing an interface modification of a negative electrode-free lithium metal battery by using ultraviolet polymerized tannic acid composite Ag particles according to claim 1, characterized in that The concentration of tannic acid in the polymerization solution is 0.2-1 g L -1 .

5. The method for preparing an interface modification of a negative electrode-free lithium metal battery using ultraviolet polymerized tannic acid composite Ag particles according to claim 1, characterized in that The concentration of hydrochloric acid in step 1 is 0.1-2 mol·L -1 .

6. The method for preparing an interface modification of a negative electrode-free lithium metal battery using ultraviolet polymerized tannic acid composite Ag particles according to claim 1, characterized in that The UV polymerization process in step 4 is carried out in a dark room.

7. The method for preparing an interface modification of a negative electrode-free lithium metal battery using ultraviolet polymerized tannic acid composite Ag particles according to claim 1, characterized in that In step 4, irradiate with ultraviolet light for 10 to 30 minutes.

8. The method for preparing an interface modification of a negative electrode-free lithium metal battery using ultraviolet polymerized tannic acid composite Ag particles according to claim 1, characterized in that The concentration of the AgNO3 solution prepared in step 5 is 1-10 mmol·L -1 .

9. The method for preparing an interface modification of a negative electrode-free lithium metal battery using ultraviolet polymerized tannic acid composite Ag particles according to claim 1, characterized in that In step six, the reaction is carried out in the AgNO3 solution for 1 to 30 minutes.

10. The method for preparing an interface modification of a negative electrode-free lithium metal battery using ultraviolet polymerized tannic acid composite Ag particles according to claim 1, characterized in that The electrolyte used in step 7 is 1 mol·L -1 LiPF6 was dissolved in DEC / FEC (1:1, V:V) and 1 mol·L -1 LiTFSI is dissolved in one or both of the mixed electrolytes DOL / DME (1:1, V:V).

Citation Information

Patent Citations

  • Method for modifying polyolefin lithium-ion battery separator

    CN110010824A

  • Noble metal elementary substance @ nitrogen-doped carbon hollow sphere material, lithium metal negative electrode active material, lithium metal negative electrode and preparation and application of lithium metal negative electrode

    CN112447949A

  • Electrolyte film-forming additive and lithium ion battery electrolyte containing same

    CN115663392A

  • Preparation method of rare-earth-based biomimetic mineralized super-hydrophilic material

    CN116531965A